The sport of kings : kinship, class, and thoroughbred breeding in Newmarket - Cassidy, Rebecca (Cambridge University Press, 2002)
A 'behind the scenes' description of British flat racing based on the experiences of an academic living and working in Newmarket, regarded as the international headquarters of flat racing. Rebecca Cassidy offers explanations of the rituals involved in horseracing, and shows how racing, betting and the bloodstock industry fit together.